7(C+2)=3C-5+4C+9

Simple and best practice solution for 7(C+2)=3C-5+4C+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(C+2)=3C-5+4C+9 equation:


Simplifying
7(C + 2) = 3C + -5 + 4C + 9

Reorder the terms:
7(2 + C) = 3C + -5 + 4C + 9
(2 * 7 + C * 7) = 3C + -5 + 4C + 9
(14 + 7C) = 3C + -5 + 4C + 9

Reorder the terms:
14 + 7C = -5 + 9 + 3C + 4C

Combine like terms: -5 + 9 = 4
14 + 7C = 4 + 3C + 4C

Combine like terms: 3C + 4C = 7C
14 + 7C = 4 + 7C

Add '-7C' to each side of the equation.
14 + 7C + -7C = 4 + 7C + -7C

Combine like terms: 7C + -7C = 0
14 + 0 = 4 + 7C + -7C
14 = 4 + 7C + -7C

Combine like terms: 7C + -7C = 0
14 = 4 + 0
14 = 4

Solving
14 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5=4k+53 | | z/4=30 | | 2(9x-8)=19x-15 | | 5x-17=3x+10 | | 2x(5-3)-3=5 | | 4(6)+3= | | 3y+12x=-11 | | 1.1x+1.2+-5.4=-10 | | 8k(4-6)-2x=16(3-k) | | 8(2x-3)-4=6x+9x-1 | | 30x-3x=X-2 | | 6x+15-7= | | 2(2n-1)=(n+3) | | 18+8x=9(x-2) | | 2(t-6)+6t=4(2t+3)-10 | | 3(9-3x)=45 | | x-5d=3 | | 6(-4x+5)=246 | | -77=7(1+4b) | | 4+3z-2=9z+9-7z | | 12+4(z-3)=3x+1 | | 5(r+3)-6=3(r-2) | | 3n+9=-3(2n+3) | | -28=7(7n-4) | | X^2=5*x^2-36 | | X+12+5x-17=2x+11 | | 7e^7t=11e^6t | | 5a+7b=17 | | 2(y+4)=21 | | 5*x^2-36-x^2=0 | | 3x-1=4x+9 | | x(x+3)-3=3x+1 |

Equations solver categories